Acute Performance Estimation of Students Using Quantile Regression Approach (A Case Study of Lahore): Sunaina Ishtiaq* Yasar Mahmood** Hina Khan*** - Amjad Hashmi (PJE, 2023)
Extreme behavior (Performance) of students is inclined by number of factors which are must be painted for important policy implications. This study states that CGPA is the most important system to detect student performance. Data on CGPA has been collected from B.A/B.Sc (Hons.) of 32 private and public universities of Lahore. Generally, researchers investigate an average performance of the students with classical methods of simple linear regression. This approach does not give complete picture of different variables influencing student performance from corner to corner. Quantile regression introduces information across the whole distribution of the student’s achievements.